The mechanisms of photodynamic action for treating of cancer patients - A. L. Akopov; N. V. Kazakov; A. A. Rusanov; A. Karlson (Biomedical Photonics)
Current views on mechanisms of therapeutic effect of photodynamic therapy for treating of cancer patients are represented. The history of formation and development of the method is described. The main requirements for agents used as photosensitizers are listed. Detailed review of main photosensitizers used in clinical practice in Russia and in foreign countries with their chemical structure, main spectral characteristics was performed. Methods of its application, therapeutic dose ranges, indications, specifi c pharmacokinetic properties and side-effects are briefl y outlined. Advantages and disadvantages of the most popular modern photosensitizers, main mechanisms of entry of photosensitizers of different chemical structure into cancer cells are observed. Three main possible component of anti-tumor effect: direct damage of cancer cells, impairment of vascular stroma of tumor and elimination of tumor due to immune cells are shown and closely discussed. Necrosis and apotosis of neovascular net which are main development trends of anti-tumor action for photodynamic therapy are noticed.